Postoperative Analgesia with Saphenous Block Appears Equivalent to Femoral Nerve Block in ACL Reconstruction. Issue 3 (October 2014) - Chisholm, Mary F.; Bang, Heejung; Maalouf, Daniel B.; Marcello, Dorothy; Lotano, Marco A.; Marx, Robert G.; Liguori, Gregory A.; Zayas, Victor M.; Gordon, Michael A.; Jacobs, Jason; YaDeau, Jacques T.
Background: Adequate pain control following anterior cruciate ligament reconstruction (ACL) often requires regional nerve block. The femoral nerve block (FNB) has been traditionally employed. Ultrasound application to regional nerve blocks allows for the use of alternatives such as the saphenous nerve block following ACL reconstruction. Questions/Purposes: This study evaluated postoperative analgesia provided by the subsartorial saphenous nerve block (SSNB) compared to that provided by the traditional FNB for patients undergoing ACL reconstruction with patellar tendon (bone–tendon–bone (BTB)) autografts. Methods: A randomized, blinded, controlled clinical trial was conducted using 80 ASA I–III patients, ages 16–65, undergoing ACL reconstruction with BTB. The individuals assessing all outcome measures were blinded to the treatment group. Postoperatively, all patients received cryotherapy and parenteral hydromorphone to achieve numeric rating scale pain scores less than 4. At discharge, patients were given prescriptions for oral opioid analgesics and a scheduled NSAID. Patients were instructed to complete pain diaries and record oral opioid utilization. Patients were contacted on postoperative days (POD) 1 and 2 to ascertain the level of patient satisfaction with the analgesic regimen. Results: No differences between the two groups were found. Patient demographics and postoperative pain scores at rest were not different. In addition, there was no difference in opioid use, as measured in daily oral morphine equivalents between groups. A small but statistically significant report of higher patient satisfaction with the FNB was found on POD 1 but not on POD 2. Conclusion: These data support our hypothesis that the SSNB provides similar and adequate postoperative analgesia when compared to the FNB, following arthroscopic ACL reconstruction with patellar tendon autograft.